Analytical investigation of dead space effect under near-breakdown conditions in GaInP/GaAs composite double heterojunction bipolar transistors - GOH, Y; ONG, D (2004)
The dead space effect under near-breakdown conditions in GaInP/GaAs composite collector double heterojunction bipolar transistor (DHBT) is investigated analytically. Using the dead space corrected model, the breakdown voltage is found to decrease with GaAs spacer thickness as reported from experiments. The common-mode emitter IV characteristics for the DHBT are simulated until the onset of multiplication with good agreement with reported experimental results [IEEE Elec. Dev. Lett. 15 (1994) 10]. A proposed optimised structure is simulated with comparably good turn-on I V characteristics and improved breakdown performance. (C) 2004 Elsevier Ltd. All rights reserved.